Application of 18F Prostate-Specific Membrane Antigen Positron Emission Tomography/Computed Tomography in Monitoring Gastric Metastasis and Cancer Thrombi from Renal Cell Carcinoma. (4th February 2022) - Xiong, Min; Zhang, Weiguang; Zhou, Chao; Bao, Junjie; Zang, Shengbing; Lin, Xiaoping
Abstract : Background . Renal cell carcinoma (RCC) with gastric metastasis is rare, particularly accompanied by multiple cancer thrombi. Methods . We reported a 66-year-old man with a history of a right radical nephrectomy because of RCC. The patient underwent 18 F prostate-specific membrane antigen (PSMA) positron emission tomography/computed tomography (PET/CT) scanning after 6 months of targeted therapy because of gastric metastasis and cancer thrombi. We conducted a systematic review of the literature and identified 73 cases of RCC with gastric metastasis. We analyzed the clinicopathological characteristics, therapies, and outcomes of patients. Results . 18 F-PSMA PET/CT showed a large mass in the gastric fundus and cancer thrombi in the right atrium, inferior vena cava, and splenic vein with intense tracer uptake. Other metastases with increased tracer uptake included multiple bones and abdominal lymph nodes. The majority of gastric metastasis of RCC were men (53/73, 72.6%), with a median age at presentation of 67 (from 48 to 87) years. Gastric metastasis of RCC was mainly metachronous, and presented with small polyps or mass appearance and often accompanied by multiple-site metastases and gastrointestinal symptoms. An overall median interval between nephrectomy and diagnosis of gastric metastasis was 6 (from 0.1 to 23) years, and an overall median survival time was 14 (from 0.25 to 72) months. The median interval time of solitary gastric metastasis was longer than gastric metastasis with multiple-site metastases (7 vs.5 years; P = 0.034 ). Patients with gastric and multiple-site metastases had higher mortality than patients with solitary metastasis (17 vs.1; P = 0.028 ). The patients with synchronous gastric metastasis had a shorter survival time than metachronous gastric metastasis (6 vs.17 months; P = 0.018 ). Conclusions . Postoperative follow-up of multiple imaging modalities to monitor recurrence and metastasis is necessary and important. PSMA PET/CT can improve the detection sensitivity of RCC, especially in metastatic clear cell renal cell carcinoma (ccRCC), and could provide a basis for disease staging, restaging, and therapeutic efficacy evaluation.